2020
DOI: 10.1177/1558944720906494
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Management of Peripheral Intravenous Infiltration Injuries

Abstract: Background: Although intravenous (IV) infiltration is relatively common, data regarding complications and outcomes of this problem remain limited. In addition, there is wide variation in institutional protocols for the management of IV infiltrations. Through retrospective review, we aim to delineate complications and outcomes, and propose an algorithm for the management of these injuries. Methods: We performed a retrospective review of all patients who had an IV infiltration at a tertiary care center’s inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It is also hypothesized that intravenous infiltration may be under-reported due to a low rate of long-term or serious adverse complications as a result of this complicating event. A recent study by Gibian et al 7 reviewed 495 infiltration events and found that 8.6% resulted in a soft tissue infection, 3.2% experienced necrosis and 1.9% suffered ulceration. The authors further found that only 5.1% of these patients were deemed to suffer from long-term defects secondary to the infiltration.…”
Section: To the Editormentioning
confidence: 99%
“…It is also hypothesized that intravenous infiltration may be under-reported due to a low rate of long-term or serious adverse complications as a result of this complicating event. A recent study by Gibian et al 7 reviewed 495 infiltration events and found that 8.6% resulted in a soft tissue infection, 3.2% experienced necrosis and 1.9% suffered ulceration. The authors further found that only 5.1% of these patients were deemed to suffer from long-term defects secondary to the infiltration.…”
Section: To the Editormentioning
confidence: 99%
“…3,4 Furthermore, several studies have evaluated the severity of skin injuries associated with extravasation and their outcomes in clinical practice. [5][6][7] However, most are single-center studies and lack external validity. In addition, to the best of the authors' knowledge, no study has comprehensively analyzed the risks of extravasation-related adverse events (AEs), their corresponding skin injury profiles, and their outcomes according to the use of specific drugs, including those for the combination of cytotoxic and noncytotoxic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have evaluated the severity of skin injuries associated with extravasation and their outcomes in clinical practice 5–7. However, most are single-center studies and lack external validity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, the onset of symptoms may be delayed by a few days. [9][10][11][12][13] The rate of extravasation with vincristine is reported 1%-2%. 14 The diagnosis of delayed symptoms of extravasation after vincristine may be complicated.…”
Section: Introductionmentioning
confidence: 99%